2021
DOI: 10.3390/ijerph182010990
|View full text |Cite
|
Sign up to set email alerts
|

Social Distancing Policies in the Coronavirus Battle: A Comparison of Denmark and Sweden

Abstract: Social distancing measures have been a key component in government strategies to mitigate COVID-19 globally. Based on official documents, this study aimed to identify, compare and analyse public social distancing policy measures adopted in Denmark and Sweden regarding the coronavirus from 1 March 2020 until 1 October 2020. A key difference was the greater emphasis on laws and executive orders (sticks) in Denmark, which allowed the country to adopt many stricter policy measures than Sweden, which relied mostly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…The difference was particularly large in Sweden; almost twice as many respondents expressed moderately large or very large trust in the public health authority's handling than with the government's handling. This could be interpreted as high public trust in the Public Health Agency's expertise and use of voluntary recommendations [4]. These ndings are consistent with those of Nielsen and Lindvall [24], who also found that trust in the public health authorities' ability to guide the country safely through the pandemic was higher than trust in the ability of the government of each country to do so.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The difference was particularly large in Sweden; almost twice as many respondents expressed moderately large or very large trust in the public health authority's handling than with the government's handling. This could be interpreted as high public trust in the Public Health Agency's expertise and use of voluntary recommendations [4]. These ndings are consistent with those of Nielsen and Lindvall [24], who also found that trust in the public health authorities' ability to guide the country safely through the pandemic was higher than trust in the ability of the government of each country to do so.…”
Section: Discussionsupporting
confidence: 84%
“…However, Sweden's approach changed in response to high rates of COVID-19 cases when the second wave of the pandemic hit in the winter 2020-2021. This led to swift development of a Pandemic Law and adoption of many more mandatory restrictions, thus making Sweden's strategy more similar to Denmark's [4].…”
mentioning
confidence: 99%
“…In Sweden, the PHA took a leading role in pandemic management, communication and decision‐making. In Denmark, the government was the central decision‐maker, with the PHA mainly responsible for providing recommendations to the government and providing general guidelines to the population (Pashakhanlou, 2022; Seing et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…In general, the voices of the privileged positions in society have greater power than the less privileged positions, also in terms of disease understandings and defining related strategies (Boelsbjerg and Glasdam, 2022; Bourdieu, 1996; Chang et al, 2016). However, both governments (Gjerde, 2021; Nygren and Olofsson, 2021; Ortega and Orsini, 2020; Seing et al, 2021) and individuals (re)act differently when facing diseases or crises (Boelsbjerg and Glasdam, 2022; Chang et al, 2016). Individuals’ strategies related to new life situations, such as the pandemic, are based on habitus, capital, and social position in society (Bourdieu, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals’ strategies related to new life situations, such as the pandemic, are based on habitus, capital, and social position in society (Bourdieu, 1995). Individuals’ strategies are also related to the strategy of their country of residence (Seing et al, 2021; Stjernswärd et al, 2021a). The current pandemic has earned the title of ‘infodemic’ due to the massive amount of information circulating through varied channels (Gallotti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%